Generation Of Hospital Waste: An Awareness Impact on Health and Environmental Protection - Deepak Sharma (National Journal of Community Medicine, 2013)
World is generating more and more waste as the population of people in the world & Hospitals are increasing day by day. Health care activities are a means of protecting health, curing patients and saving lives. Waste generating from hospitals, health centers and medicals are no exceptions. Medical waste contains toxic chemicals, can be infectious and pose contamination risks both to public health and environment. But they also generate waste, out of which 25 percent entail risks, either of infection, of trauma or radiation exposure. In addition the inappropriate treatment or disposal of the waste can lead to environmental contamination or pollution. Seventy five percent of the hospital waste is similar to household waste and do not entail any particular hazard. In general, PVC plastic waste represents the large amount in hospital waste. In this paper we are addressing the issue of incineration of medical waste and to control the surface water mercurial pollution, their impacts on health, environment and their remediation.